Scorpions! : strange and wonderful - Pringle, Laurence, 1935- (Pringle, Laurence, 1935- Strange and wonderful., 2013)
Challenges popular fear-based assumptions and reveals how most of the world's scorpion species are not dangerous and only sting to subdue prey or protect themselves. Provides vivid descriptions of scorpion life cycles, habits and characteristics.